Hubungan Self-Efficacy dan Motivasi Belajar dengan Kemampuan Koneksi Matematis Mahasiswa - Putri Dwitasari; Ayoudya Shakthi Pratama; Irza As-sajdah Tulloh; Netriwati Netriwati; Fadly Nendra (Pendidikan Matematika FKIP Universitas Mataram, 2026)
This study aims to examine the relationship between self-efficacy and learning motivation with students’ mathematical connection ability. The background of this research is the low ability of students to connect mathematical concepts, especially in higher education. This study used a quantitative approach with a correlational design involving 50 sixth-semester students who had taken a Basic Statistics course. Data were collected through self-efficacy and learning motivation questionnaires, as well as a mathematical connection ability test. The data were analyzed using descriptive statistics and inferential statistics, with the Spearman correlation test applied due to non-normal data distribution. The results showed that learning motivation has a significant relationship with mathematical connection ability, while self-efficacy does not show a significant relationship. The contribution of learning motivation to mathematical connection ability is greater compared to self-efficacy. These findings indicate that learning motivation plays a more dominant role in improving students’ ability to connect mathematical concepts. Therefore, efforts to enhance students’ motivation are essential in supporting better mathematical understanding.